Preliminary Results of Feasibility and Acceptability of Self-Collection for Cervical Screening in Italian Women - Illari Sechi; Narcisa Muresu; Mariangela V. Puci; Laura Saderi; Arcadia Del Rio; Andrea Cossu; Maria R. Muroni; Santina Castriciano; Marianna Martinelli; Clementina E. Cocuzza; Giovanni Sotgiu; Andrea Piana (Pathogens, 2023)
Background: Given the diagnostic accuracy of HPV-DNA tests in terms of self-collected samples, in order to implement self-sampling in cervical screening programs, the standardization of the pre-analytical phase, including decisions concerning the choice of medium, the volume of elution, and storage conditions, are necessary, in addition to understanding the potential factors involved in acceptability by women. On this basis, we carried out a cross-sectional study to assess (i) the stability of dry vaginal self-collected samples stored at room temperature for up to 4 weeks after elution in 2 mL of eNat® (Copan) medium, and (ii) the acceptability of self-collection in enrolled women. Methods: 185 women were enrolled in the LILT (Italian League Against Tumors) regional project. A self-sampling kit, including a dry FLOQSwab® (Copan), instructions for use, and a satisfaction questionnaire, were supplied for each woman and sent by mail to the laboratory. The HPV-DNA test was carried out using the Anyplex™ II HPV HR (Seegene) kit. To evaluate the specimen’s stability, 185 dry vaginal swabs were eluted in eNat®, a lyses-based molecular medium and tested for HPV detection at two different time points (<6 days and 1 month after elution). The Cohen’s Kappa coefficients and McNemar test were used to assess the agreement of HPV-DNA at different times. Results: We found high agreement in terms of HPV-DNA results among the samples tested at two different time points (Cohen K = 0.98; p < 0.0001). Moreover, most of the women found it easy to use self-collection devices and the pictorial instructions clear to understand. Approximately half of the enrolled women declared preferring self-sampling to clinician-collected methods. Conclusion: Our results display the high reliability and accuracy of HPV-DNA tests using dry vaginal self-collection FLOQSwabs® devices eluted in 2 mL of molecular medium. The analysis of the questionnaire showed a high acceptability of self-collection among women, although a high percentage preferred standard collection devices. Overall, our preliminary results support the adoption of self-collection in screening programs, even though further analyses should be performed to optimize and standardize protocols for HPV tests on self-samples, and educational campaigns are needed to adequately inform and increase responsiveness in a target population.